EVALUATION OF THE LEVEL OF QUALITY OF LIFE IN PATIENTS WITH BULLOUS EMPHYSEMA OF THE LUNGS AFTER SURGICAL TREATMENT - E. A. Drobyazgin; Yu. V. Chikinev; V. F. Khusainov; K. I. Shcherbina; A. S. Polyakevich (Сибирский научный медицинский журнал, 2020)
The purpose of the study was to assess the level of quality of life in the postoperative period in patients with bullous emphysema of the lungs operated on by «open» access and using minimally invasive technologies using the SF-36 questionnaire. Material and methods. The results of a survey of 50 patients with bullous emphysema were analyzed. The patients were separated into 2 groups depending on the method of access. The first group (main) consisted of the patients underwent video-assisted thoracoscopy, resection of a bulla-modified lung tissue, subtotal parietal pleurectomy. The second group (comparison) consisted of the patients underwent thoracotomy, resection of a bulla-modified lung tissue, subtotal parietal pleurectomy. The survey was conducted using the SF-36 quality of life questionnaire for 1, 3, 6 and 12 months. Results and discussion. The main indicators of the quality of life of respondents in terms of 1, 3 and 6 months after the intervention were statistically significantly higher in the group of patients who underwent thoracoscopy. Only a year after the operation, the main indicators of the questionnaire were not statistically significantly different between groups of patients, but the indicators of vital activity, social functioning, mental health and psychological component of health remained significantly higher in patients of group 1. The results indicate the need for long-term postoperative rehabilitation of patients with bullous emphysema lungs, operated in an «open» way. Follow-up survey with the specific questionnaires is required for more detailed assessment of the level of quality of life in patients with thoracic organs pathology.